Assessment and reduction of zenith path delay biases due to day boundary effect - Nguyen Ngoc, Lau; Coleman, Richard (Vietnam Journal of Earth Sciences, 2021)
The troposphere consists of dry air and water vapor, delaying the GNSS signal by about 2.4 m in the zenith direction. The water vapor only causes an error of about 0.2 m in distance measurement, but it is challenging to model and overcome. From 2003 the International GNSS Service (IGS) started to provide the new product of zenith path delay (ZPD) with an accuracy of 1.5-5 mm. However, we found an error in these products up to 30 mm at epochs between 2 days due to the day boundary effect and an average of 16mm RMS for nine days. Our research shows that for reducing the impact, the most critical factor is selecting the initial value for the ZPD, followed by satellite orbit/clock and, finally, the station coordinate values. By choosing an appropriate initial value for ZPD and employing a 3 days orbit/clock, the ZPD error due to the day boundary effect can be reduced to negligible. Meanwhile, the change in the station coordinate value in cm level does not impact the effect.